2014
DOI: 10.5395/rde.2014.39.3.149
|View full text |Cite
|
Sign up to set email alerts
|

In vitrocytotoxicity of four calcium silicate-based endodontic cements on human monocytes, a colorimetric MTT assay

Abstract: ObjectivesThis study was performed to evaluate the cytotoxicity of four calcium silicate-based endodontic cements at different storage times after mixing.Materials and MethodsCapillary tubes were filled with Biodentine (Septodont), Calcium Enriched Mixture (CEM cement, BioniqueDent), Tech Biosealer Endo (Tech Biosealer) and ProRoot MTA (Dentsply Tulsa Dental). Empty tubes and tubes containing Dycal were used as negative and positive control groups respectively. Filled capillary tubes were kept in 0.2 mL microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
2
18
0
5
Order By: Relevance
“…Mori et al [17] microscopically observed that the Biodentine inflammatory reaction at rats subcutaneous tissue had a moderate intensity at 7 analysis days, but at 30 days, the reaction was discrete or insignificant, and similar to MTA. These results agree with Khedmat et al [18] that observed similar cytotoxicity from both material on human monocytes, by the MTT assay.…”
Section: Discussionsupporting
confidence: 83%
“…Mori et al [17] microscopically observed that the Biodentine inflammatory reaction at rats subcutaneous tissue had a moderate intensity at 7 analysis days, but at 30 days, the reaction was discrete or insignificant, and similar to MTA. These results agree with Khedmat et al [18] that observed similar cytotoxicity from both material on human monocytes, by the MTT assay.…”
Section: Discussionsupporting
confidence: 83%
“…Both MTA and BD demonstrated being non-cytotoxic and did not present a significant difference with regard to viability at 24 and 48 h; at 48 h, cells grown in the presence of MTA and BD possessed a higher percentage of viability than the groups treated with other cements, but there were no significant differences between BD and MTA ( p < 0.05) [1719]. …”
Section: Discussionmentioning
confidence: 99%
“…The MTT assay is a well-established method of determining cell viability and has been used in previous studies to test the cytotoxicity of dental adhesives and other dental materials because it is simple, fast, and objective (Costa et al, '99;Issa et al, 2004;Goldberg, 2008;Huang et al, 2010;Kusdemir et al, 2011;Khedmat et al, 2014;Lee et al, 2015). According to the MTT assay, the control group showed the highest odontoblast viability, followed by the SB, IB, XV, AO, CS, and EB groups.…”
Section: Discussionmentioning
confidence: 99%